L’Épître de Jacques dans sa tradition d’exégèse. Edited by Matthieu Arnold, Gilbert Dahan, and Annie Noblesse-Rocher - Evans, Gillian (The journal of theological studies, 2013)
This is an experiment in tracing the exegetical history not of a single text or a pericope but of a whole book of the Bible. The Epistle of James was controversial in the early Christian centuries because some doubted its authenticity. The challenge was mounted again in the sixteenth century, for example by Erasmus. The chief objection to this ‘book of straw’ in Luther’s eyes was that it contains texts which seem irreconcilable with a doctrine of justification by faith alone.